Analysis of the potential of base and non-base sectors in Blora regency: location quotient, shift-share and klassen typology methods - Oktaviana Arsita; Happy Adianita (Jurnal Mantik, 2024)
The instability of a region's economic growth is caused by internal and external factors. In the 2016-2022 period, one of the external factors is the impact of the Covid-19 outbreak and internal factors are seen from the realisation of the utilisation of regional potential and the role of the existing sectors in each region. With the potential and role of different sectors in each region, a study of economic potential is needed. In line with the research objectives, namely determining the basic and non-basic sectors and their growth typology by increasing the comparative advantage of the economic sector in order to determine the specialisation and competitiveness of a region. This can be identified through the Location Quotient (LQ) method with results indicating that in Blora Regency there are nine basic sectors, the remaining eight are non-basic sectors, which means that Blora Regency has many sector options that can be the focus of the government. The sector with the largest capacity is the mining and quarrying sector. The contribution of a sector and its shift is identified by Shift-Share method with the overall calculation that the competitiveness and competitive advantage of this region is higher than Central Java Province. To see the sector classification of an economy, the Klassen Typology method is used.